2023
DOI: 10.3389/fphar.2023.1297124
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Salvianic acid A against multiple-organ ischemia-reperfusion injury: a review

Shiyu Yang,
Heming Chen,
Wei Su
et al.

Abstract: Ischemia-reperfusion (I/R) injury refers to a new injury caused by reperfusion after the restoration of ischemic tissue or organ blood supply. Salvianic acid A (danshensu) is a primary active ingredient extracted from Salvia miltiorrhiza. It has a protective function against I/R injury in the cardiovascular system, brain, liver, kidney, gastrointestinal tract, and other organs. This article reviews evidence of the protective effects of Salvianic acid A and its potential mechanisms of action in organ I/R injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…Therefore, nanodelivery technology must be chosen to effectively target and deliver DSS to the brain. Importantly, our group has previously demonstrated that DSS treatment inhibits oxidative stress, suppresses inflammatory reactions, and decreases neuronal apoptosis in rats, suggesting its potential as a human stroke treatment candidate. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, nanodelivery technology must be chosen to effectively target and deliver DSS to the brain. Importantly, our group has previously demonstrated that DSS treatment inhibits oxidative stress, suppresses inflammatory reactions, and decreases neuronal apoptosis in rats, suggesting its potential as a human stroke treatment candidate. , …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, our group has previously demonstrated that DSS treatment inhibits oxidative stress, suppresses inflammatory reactions, and decreases neuronal apoptosis in rats, suggesting its potential as a human stroke treatment candidate. 20,21 In this study, we prepared a three-dimensional (3D) thioketal cross-linked chitosan with carboxyl groups and carboxymethyl β-cyclodextrin network to enhance the efficiency of loading DSS and control its release into injured cerebral regions. This 3D network was first chemically synthesized by linking CS with ketal; subsequently, carboxymethyl β-cyclodextrin were added to form the network.…”
Section: Introductionmentioning
confidence: 99%